Don't think of a wave! A research note about the current autocratization debate. Issue 6 (18th August 2021) - Tomini, Luca
ABSTRACT: One of the most fascinating developments in the recent comparative politics scholarship is undoubtedly the turn from the studies on the process of democratization to those on the opposite phenomenon, that is, autocratization. After the recent, initial wave of empirical studies, only recently scholars began to tackle some underlying albeit essential issues, such as the problem of conceptualization and measurement of this concept. On the pages of Democratization, a crucial debate recently emerged when Svend-Erik Skaaning reacted to the high-impact 2018 article by Anna Lührmann and Staffan Lindberg. This piece aims to contribute to this stimulating debate. The main message of this piece is: don't think of a wave! Autocratization matters and deserves to be studied, even if there is no such a "third wave." This research note claims that steering the debate on the concept of wave(s ), which is of limited analytical and explanatory power, is misleading and risks taking the entire discussion down a blind alley. In the second part, the research note discusses some of the open issues of this literature, and in particular a) the very conceptualization of autocratization and b) the problem of thresholds and false positives. In the same way, the third part deals with three new areas of inquiry: c) the multi-dimensional nature of autocratization d) the multi-level dimension of autocratization and e) the opposition to autocratization.